Scalable and thermally-integrated solar water-splitting modules using Ag-doped Cu(In, Ga)Se2 and NiFe layered double hydroxide nanocatalysts. Issue 22 (19th May 2022) - Bayrak Pehlivan, İlknur and Saguì, Nicole A. and Oscarsson, Johan and Qiu, Zhen and Zwaygardt, Walter and Lee, Minoh and Mueller, Martin and Haas, Stefan and Stolt, Lars and Edoff, Marika and Edvinsson, Tomas
Abstract : A thermally-integrated solar water-splitting approach is presented, using bifunctional precious metal free catalysts based on Fe and Ni. The approach is scalable and reaches up to 13.4% solar-to-hydrogen (STH) efficiency. Abstract : Photovoltaic (PV) electrolysis is an important and powerful technology for environmentally-friendly fuel production based on solar energy. By directly coupling solar cell materials to electrochemical systems to perform water electrolysis, solar energy can be converted into hydrogen fuel utilizing locally-generated heat and avoid losses from DC–DC convertors and power grid transmission. Although there have been significant contributions to the photoelectrochemical and PV-electrolysis field using isolated laboratory cells, the capacity to upscale and retain high levels of efficiency in larger modules remains a critical issue for widespread use and application. In this study, we develop thermally-integrated, solar-driven water-splitting device modules using AgCu(In, Ga)Se2 (ACIGS) and an alkaline electrolyzer system with NiFe-layered double hydroxide (LDH) nanocatalysts with devices of 82–100 cm 2 area. The Ga-content in the ACIGS solar cells is tuned to achieve an optimal voltage for the catalyst system, and the average efficiencies and durability of the PV-electrolyzer were tested in up to seven-day indoor and 21 day outdoor operations. We achieved a solar-to-hydrogen (STH) module efficiency of 13.4% from gas volume measurements for the system with a six-cell CIGS-electrolyzer module with an active area of 82.3 cm 2 and a 17.27% PV module efficiency under 100 mW cm −2 illumination, and thus 77% electricity-to-hydrogen efficiency at one full sun. Outdoor tests under mid-Europeen winter conditions exhibited an STH efficiency between 10 and 11% after the initial activation at the installation site in Jülich, Germany, in December 2020, despite challenging outdoor-test weather conditions, including sub-zero temperatures.